Radionuclide biosorption by the aquatic plants of Pistia stratiotes - Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Yu.V.; Medvedev, D.V.; Medvedeva, E.P.; Botova, M.A.; Khlapova, N.P.; Fedorets, I.D. (Вопросы атомной науки и техники, 2014)
The activity of leaves and roots of Pistia stratiotes from the Seversky Donets river has been measured. The visible activity of ¹³¹I in roots of plant is found. The content estimate of ¹³¹I in water of Seversky Donets river before extraction of samples of a hydrophyte gives value exceeding 1 Bk/l. The detection of activity of ¹³¹I in roots of Pistia stratiotes can be used for its monitoring in the biosphere. The photoactivation analysis has been used for measuring of element content in leaves and roots of Pistia stratiotes. Accumulation in roots versus leaves of Pistia stratiotes Mn, Co, Ni, Mo, I, Pb and also isotopes ²²⁸Ac, ²¹⁴Pb and ²¹⁴Bi was detected.